DZNep and UNC0642 enhance in vitro developmental competence of cloned pig embryos. Issue 4 (April 2018) - Zhao, Chengfa; Shi, Junsong; Zhou, Rong; He, Xiaoyan; Yang, Huaqiang; Wu, Zhenfang
Abstract : Somatic cell nuclear transfer in mammalian cloning suffers from a faulty epigenetic reprogramming, which is believed to cause developmental failures in cloned embryos. Regulating the epigenetic-modifying enzymes can rescue the chromatin of cloned embryos from aberrant epigenetic status, thereby potentially promoting cloning efficiency. In this study, we investigated the effect of two histone methyltransferase inhibitors, namely, DZNep and UNC0642, on the in vitro developmental competence of cloned pig embryos. We found that (1) treatment with 10 nM DZNep or 5 nM UNC0642 for 24 h after activation had the best promoting effect on the development of cloned embryos (blastocyst rate 10.32% vs 18.08% for DZNep, and 10.44% vs 18.14% for UNC0642); (2) 10 nM DZNep and 5 nM UNC0642 significantly decreased the levels of H3K27me3 and H3K9me2, respectively, at the 2-cell, 4-cell and blastocyst stages; (3) the apoptosis level was lower in the treatment groups than in untreated control; and (4) the transcriptional expression of epigenetic genes ( EZH2, GLP, G9a, Setdb1, Setdb2, Suv39h1 and Suv39h2 ) was decreased and pluripotency genes ( Nanog, Pou5f1, Sox2 and Bmp4 ) was increased in treatment groups compared with control. These results indicated that treatment with DZNep and UNC0642 improves the epigenetic reprogramming of cloned embryos, which could render beneficial effect on the embryo quality and aberrant gene expression, and finally improve the developmental competence of cloned pig embryos.